Exploratory and confirmatory analysis of the empathy scale of empathy in inmates for the crime of violation of sexual freedom of sexual freedom of minors in a penitentiary penitentiary institution of Metropolitan Lima - Canales Bernales, Martha Leslie (2016)
The objective of this work is to know the approximation of the psychometric properties of the Empathy Scale Situation C (part and b). The scale was administered to 256 inmates for the crime of violation of the sexual freedom of minors of a penitentiary institution of Metropolitan Lima, whose ages oscillated between 18 to 67 years. The results reveal a reliability, using Cronbach’s Alpha, for the total scale of 0.95. The factors of part a (aggressor thoughts) and b (feelings of aggressor) have reliability indexes of 0.96 and 0.92, respectively. All reliability coefficients are considered excellent. The exploratory factor analysis on both sides indicated that four factors underlie the items, while the goodness of fit to the model proposed by confirmatory factor analysis satisfactorily verify the empathy construct for the sample. It is concluded that the Empathy Scale has adequate psychometric properties, and it is recommended to carry out confirmatory factorial analysis in order to verify the internal structure.